Evaluation of the efficiency of biological and economic indicators in production systems on dairy farms - Londoño-Franco, Luis Fernando; Marini, Pablo Roberto (Revista de Ciencias Agrícolas, 2023)
The efficiency of the livestock system is one of the factors of greatest social and economic interest in rural production areas. The project aimed to assess various biological and economic indicators to identify the most efficient dairy cows in grazing systems with supplementation within the Antioquia-Colombia dairy basin. We used retrospective data from 2009 to 2019 from farms in the municipalities of Entrerríos, San Pedro, and Belmira. The production systems in the northern region of Antioquia share common features typical of many dairy enterprises. They are primarily characterized by their utilization of grazing systems, each employing distinct supplementation regimes.The farms have their own records and official milk control from the cooperatives or associations from which the data was obtained. The productive categories of the evaluated cows were established according to the number of births, and within each subgroup, they were ordered by the total liters per lactation in ascending order. Productive, reproductive, health, and economic variables were recorded. Then cuts were made, thus forming three categories: low, medium, and high production. It was possible to determine the model that showed four groups of variables (breed, milk production per lactation, open days, and silage) with an important correlation of 97% and a greater contribution to the behavior of the cost per liter, obtaining an R2 of 0.91 (P <0.05) and a prediction error of US 0.0076 per liter of milk in the evaluated farms. It is concluded that, with few biological and economic predictive indicators, it was possible to identify the most efficient cows in grazing systems.